The effect of chamomile tea consumption on inflammation among rheumatoid arthritis patients: randomized clinical trial - Pirouzpanah, Saeed; Mahboob, Soltanali; Sanayei, Mahzad; Hajaliloo, Mehrzad; Safaeiyan, Abdolrasoul (Progress in Nutrition, 2017)
Background: Rheumatoid arthritis (RA) is a joint inflammatory disease, which proinflammatory cytokines and oxidant spices accelerate inflammatory response in patients. Drugs and supplements which can modulate the inflammation can slow the disease progression, and minimize the joints destruction. Anti inflammatory effect of Chamomile on severity of disease was measured by Disease Activity Score (DAS-28) tool in the study. Patients and method: The study was a randomized, placebo-controlled, double blind clinical trial. The participants were selected from Tabriz university rheumatology clinic clients. According to rheumatologist diagnosis, 44 patients have the inclusion criteria in this study which fulfilled the American college of rheumatology (ACR-2010) criteria, were included.The patients were randomized in two groups, receiving 6 g/day Chamomile tea as 2 teabags twice a day for 42 days or placebo teabags, containing as similar. DAS-28 as an identified variable was calculated. For this, erythrocyte sedimentation rate (ESR) was measured before and after the study. Also all the patients were clinically examined, in order to determine the tender joints and swollen joints number. They reported the pain by Visual Analogue Scale (VAS). Nutrition intake was measured at both times in order to minimize the cofounders. Results: Groups were matched at the beginning in demographic characteristics, such weight height, age and BMI. During the intervention BMI didn’t change, but tender joints number and ESR changed significantly (P=0.000 and P=0.018, respectively). Conclusion:  This study showed that Chamomile could decrease the inflammation similar to cell studies before. It can be a complementary treatment for RA patients.